2020
DOI: 10.1177/0363546520949541
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Treatment of Cam Morphology May Change the Natural History of Femoroacetabular Impingement

Abstract: Background: There is debate in the literature whether cam morphology is associated with increased risk for hip osteoarthritis. The capability of femoroplasty to alter the natural history of cam morphology is still in question. Purpose: To (1) investigate the correlation between cam morphology and damage to the articular cartilage and (2) assess whether correction of the cam morphology affects survivorship of the joint, progression to arthroplasty, and functional patient-reported outcome scores. Study Design: C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 32 publications
2
32
0
1
Order By: Relevance
“…This interpretation of the FIRST trial results is supported by another recent AJSM publication by Domb et al 4 In that retrospective cohort study, the authors divided hip arthroscopy patients into 3 matched groups according to their pre- and postoperative alpha angle measurements: those whose alpha angle was <50° both before and after surgery, those whose alpha angle was >55° before surgery and <50° afterward, and those whose alpha angle was >55° both before and after surgery. At the time of surgery, both groups with elevated preoperative alpha angles, which averaged 66°-69°, were noted to have more labral and acetabular cartilage damage than the third group, whose mean preoperative alpha angle was only 50°.…”
mentioning
confidence: 69%
“…This interpretation of the FIRST trial results is supported by another recent AJSM publication by Domb et al 4 In that retrospective cohort study, the authors divided hip arthroscopy patients into 3 matched groups according to their pre- and postoperative alpha angle measurements: those whose alpha angle was <50° both before and after surgery, those whose alpha angle was >55° before surgery and <50° afterward, and those whose alpha angle was >55° both before and after surgery. At the time of surgery, both groups with elevated preoperative alpha angles, which averaged 66°-69°, were noted to have more labral and acetabular cartilage damage than the third group, whose mean preoperative alpha angle was only 50°.…”
mentioning
confidence: 69%
“…The three major osseous factors for the development of FAI are often seen in combination and not as isolated entities [19]. When evaluated individually, the literature shows that the risk of subsequent hip osteoarthritis is highest in the presence of a cam deformity, while this association is less well established for isolated pincer deformities and abnormal femoral antetorsion [1].…”
Section: Biomechanical Conceptsmentioning
confidence: 99%
“…Moreover, in patients scheduled for surgery, the assessment of joint damage allows the stratification of patients into those with only minor and peripheral joint damage -these individuals can expect a good long-term outcome after arthroscopic surgery. Patients with more central lesions of the articular cartilage or widespread joint damage may choose to undergo surgery for pain relief, but the surgical procedure will not allow to prevent or delay osteoarthritis in those patients [1].…”
Section: Assessing Joint Damage In Faimentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas most recently, level of evidence increased indicating that cam morphology of femoral head (asphericity) leads to development of hip osteoarthritis due to acetabular chondral damage (3)(4)(5)(6)(7) . Supporting this, Domb et al (7) also reported that in patients treated with hip arthroscopy and optimal resection, cam deformity (postoperative α angle<55 0 ) had lower incidence of conversion to total hip arthroplasty than incomplete resection (postoperative α>55 0 ). A recent in vitro study also confirmed that accurate cam resection restored normal peak joint contact stresses (8) .…”
Section: Introductionmentioning
confidence: 99%